Fossil-fuelled power generation during haze - Palanichamy, Chinnasamy (2015)
Malaysia is facing haze problems for many years and the Government's major budget has been utilized for eradicating this issue so as to provide a healthy environment for its people. Apart from the peat and forest fires, the electricity generation through fossil-fuelled power stations also significantly contributes to the environmental issues in Malaysia. For the sustainable development of the country and to become a prime land in the Asean region, the Government of Malaysia has to pay more attention to exterminate the ongoing haze problem. During haze, as the power plant emissions augment the environmental issues, two operational strategies of fossil-fuelled power stations are presented to reduce their emissions. The efficacy of the proposed strategies has been demonstrated through a 24-bus, 11 fossil-fuelled generator test system at different load conditions during a 24-hour period.